Accessing In Situ Photocorrosion under Realistic Light Conditions: Photoelectrochemical Scanning Flow Cell Coupled to Online ICP-MS - Jenewein, Ken; Kormányos, Attila; Knöppel, Julius; Mayrhofer, Karl; Cherevko, Serhiy (ACS Measurement Science Au, 2021)
High-impact photoelectrode materials for photoelectrochemical (PEC) water splitting are distinguished by synergistically attaining high photoactivity and stability at the same time. With numerous efforts toward optimizing the activity, the bigger challenge of tailoring the durability of photoelectrodes to meet industrially relevant levels remains. In situ photostability measurements hold great promise in understanding stability-related properties. Although different flow systems coupled to light-emitting diodes were introduced recently to measure time-resolved photocorrosion, none of the measurements were performed under realistic light conditions. In this paper, a photoelectrochemical scanning flow cell connected to an inductively coupled plasma mass spectrometer (PEC-ICP-MS) and equipped with a solar simulator, Air Mass 1.5 G filter, and monochromator was developed. The established system is capable of independently assessing basic PEC metrics, such as photopotential, photocurrent, incident photon to current efficiency (IPCE), and band gap in a high-throughput manner as well as the in situ photocorrosion behavior of photoelectrodes under standardized and realistic light conditions by coupling it to an ICP-MS. Polycrystalline platinum and tungsten trioxide (WO3) were used as model systems to demonstrate the operation under dark and light conditions, respectively. Photocorrosion measurements conducted with the present PEC-ICP-MS setup revealed that WO3 starts dissolving at 0.8 VRHE with the dissolution rate rapidly increasing past 1.2 VRHE, coinciding with the onset of the saturation photocurrent. The most detrimental damage to the photoelectrode is caused when subjecting it to a prolonged high potential hold, e.g., at 1.5 VRHE. By using standardized illumination conditions such as Air Mass 1.5 Global under 1 Sun, the obtained dissolution characteristics are translatable to actual devices under realistic light conditions. The gained insights can then be utilized to advance synthesis and design approaches of novel PEC materials with improved photostability.
CRIS-Team Scopus Importer:2023-03-29
Keywords: ICP-MS; photocorrosion; photoelectrochemistry; scanning flow cell; solar simulator

Automated high-throughput activity and stability screening of electrocatalysts - Jenewein, Ken; Akkoc, Gun D.; Kormányos, Attila; Cherevko, Serhiy (Chem Catalysis, 2022)
Common high-throughput (HT) approaches rapidly assess the activity of electrocatalyst libraries toward electrochemical conversion reactions. The short time regime on which individual measurements are performed creates a false perception of catalyst durability, masking the true catalyst performance by the omission of detailed stability assessments during HT campaigns. Here, an automated scanning flow cell coupled to an inductively coupled plasma mass spectrometer was developed, allowing a simultaneous HT determination of the catalyst activity and stability. Fe-Ni and Fe-Ni-Co oxide libraries were automatically synthesized by a custom-programmed pipetting robot and examined as an oxygen evolution catalyst in neutral media, the advancement of which remains a great challenge. Ni-rich compositions in Fe-Ni oxides show higher activity but also significant catalyst loss due to the major Ni dissolution, which triggers Fe dissolution. Co-rich compositions in Fe-Ni-Co oxides attain the best synergy between activity and stability.
CRIS-Team Scopus Importer:2022-11-04
Keywords: automation; high-throughput; ICP-MS; in situ stability; liquid-handling robot; oxygen evolution; scanning flow cell; SDG7: Affordable and clean energy; transition metal oxides

Dissolution of WO3 modified with IrOx overlayers during photoelectrochemical water splitting - Jenewein, Ken; Knöppel, Julius; Hofer, André; Kormanyos, Attila; Mayerhöfer, Britta; Speck, Florian; Bierling, Markus; Thiele, Simon; Bachmann, Julien; Cherevko, Serhiy (SusMat, 2023)
WO3, an abundant transition metal semiconductor, is one of the most discussed materials to be used as a photoanode in photoelectrochemical water-splitting devices. The photoelectrochemical properties, such as photoactivity and selectivity of WO3 in different electrolytes, are already well understood. However, the understanding of stability, one of the most important properties for utilization in a commercial device, is still in the early stages. In this work, a photoelectrochemical scanning flow cell coupled to an inductively coupled plasma mass spectrometer is applied to determine the influence of co-catalyst overlayers on photoanode stability. Spray-coated WO3 photoanodes are used as a model system. Iridium is applied to the electrodes by atomic layer deposition in controlled layer thickness, as determined by ellipsometry and x-ray photoelectron spectroscopy. Photoactivity of the iridium-modified WO3 photoanodes decreases with increasing iridium layer thickness. Partial blocking of the WO3 surface by iridium is proposed as the main cause of the decreased photoelectrochemical performance. On the other hand, the stability of WO3 is notably increased even in the presence of the thinnest investigated iridium overlayer. Based on our findings, we provide a set of strategies to synthesize nanocomposite photoelectrodes simultaneously possessing high photoelectrochemical activity and photostability.<br

High-throughput exploration of activity and stability for identifying photoelectrochemical water splitting materials - Jenewein, Ken; Thienhaus, Sigurd; Kormanyos, Attila; Ludwig, Alfred; Cherevko, Serhiy (Chemical Science, 2022)
The experimental high-throughput (HT) exploration for a suitable solar water splitting photoanode has greatly relied on photoactivity as the sole descriptor to identify a promising region within the searched composition space. Although activity is essential, it is not sufficient for describing the overall performance and excludes other pertinent criteria for photoelectrochemical (PEC) water splitting. Photostability in the form of (photo)electrocatalyst dissolution must be tracked to illustrate the intricate relation between activity and stability for multinary photoelectrocatalysts. To access these two important metrics simultaneously, an automated PEC scanning flow cell coupled to an inductively coupled plasma mass spectrometer (PEC-ICP-MS) was used to study an Fe-Ti-W-O thin film materials library. The results reveal an interrelation between composition, photocurrent density, and element-specific dissolution. These structure-activity-stability correlations can be represented using data science tools like principal component analysis (PCA) in addition to common data visualization approaches. This study demonstrates the importance of addressing two of the most important catalyst metrics (activity and stability) in a rapid and parallel fashion during HT experiments to adequately discover high-performing compositions in the multidimensional search space.
CRIS-Team WoS Importer:2022-12-02